2017
DOI: 10.15561/20755279.2017.0307
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Yoga means on students’ biological age indicators

Abstract: Purpose:to determine effectiveness of Yoga means' implementation in students' physical education programs. Material:in experiment 85 2nd year students participated, who were divided in control group (CG, n=43, 15 boys and 28 girls) and experimental group (EG, n=42, 17 boys and 25 girls). Their calendar age was 18-19 years. By state of health all students were in main health group (without health problems). The researches were carried out during one academic semester and implied finding and comparing of student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…The feasibility of the proposed exercises is consistent with the interests of students in this type of study, which confirms the results of our previous studies [40]. New is the data on the peculiarities of studying the means of yoga in order to improve certain physical qualities, in particular, the flexibility of female students of pedagogical specialties.…”
Section: Discussionsupporting
confidence: 89%
“…The feasibility of the proposed exercises is consistent with the interests of students in this type of study, which confirms the results of our previous studies [40]. New is the data on the peculiarities of studying the means of yoga in order to improve certain physical qualities, in particular, the flexibility of female students of pedagogical specialties.…”
Section: Discussionsupporting
confidence: 89%
“…The findings of the study indicated that the flexibility of the spine and the hamstring muscles could increase as a result of regular yoga exercises. (Sereda et al, 2020) [11] studied the Impact of Yoga Practice on the development of flexibility among the female students. The experiment was attended by 96 first-year students who were divided into control and experimental groups.…”
Section: Yoga For Flexibilitymentioning
confidence: 99%
“…Recently the classroom physical education often uses such means that do not require too much inventory or equipment and special premises here include yoga [8,16], frisbee, badminton, darts, floorball [6], calenetics [2,13] and other types of motor activity [5,14,15]. Effective means of physical education students are nontraditional game Ringo not yet very common but is quickly gaining popularity among children and young people, students, workers Poland, Russia, Ukraine, Belarus and many other countries.…”
Section: Literature Reviewmentioning
confidence: 99%